2002
DOI: 10.1590/s0037-86822002000500001
|View full text |Cite
|
Sign up to set email alerts
|

Mercury exposure and malaria prevalence among gold miners in Pará, Brazil

Abstract: Economic development, including resource extraction, can cause toxic exposures that interact with endemic infectious diseases. Mercury is an immunotoxic metal used in the amalgamation of gold, resulting in both occupational exposures and environmental pollution. A cross-sectional medical survey was conducted in 1997 on 135 garimpeiros in Para, Brazil, because of their risks of both mercury exposure and malaria transmission. Mean levels of blood and urine mercury were well above non-exposed background levels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
2
22
0
1
Order By: Relevance
“…Urine mercury levels (4 μg/L) were lower than those found in other mining populations in Amazonia [25,26,40] (Figure 1C). Only 6 had levels ≥25 μg/L, the median value found by us in another gold mine population [40]. This may have been due to the timing of our visit, during the dry season, when gold amalgamation activities were reduced.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Urine mercury levels (4 μg/L) were lower than those found in other mining populations in Amazonia [25,26,40] (Figure 1C). Only 6 had levels ≥25 μg/L, the median value found by us in another gold mine population [40]. This may have been due to the timing of our visit, during the dry season, when gold amalgamation activities were reduced.…”
Section: Resultsmentioning
confidence: 56%
“…We have reported a suggested correlation between mercury exposures and number of past malaria infections among gold miners in another gold mine settlement, in Brazil, at Piranha [40]. We have also reported that exposure of mice to low levels of mercury both decreases host resistance to murine malaria ( Plasmodium yoelii ) and impairs acquisition of immunity to murine malaria in the Nussenzweig model [47].…”
Section: Discussionmentioning
confidence: 99%
“…Rio-Rato is a gold mining site, and participants were directly involved in some aspect of gold extraction or refining, as described previously (Silbergeld et al, 2002; Silva et al, 2004). Urine mercury concentrations ranged from below the LOD (0.50 µ g Hg/L urine) to 81.4 µg Hg/L urine, with a median value of 3.67 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…33,34 In fact, malaria prevalence in Granada (3.6%) 26 is far lower than that measured in mining areas (13.8-35.0%). [34][35][36] However, the "just-in-time" hypothesis of DBP exposure 37 does not completely explain the large proportion of individuals who remain unresponsive to DBP after prolonged exposure to malaria, especially because a few dominant DBP II haplotypes seem to account for the majority of P. vivax infections in areas of high malaria transmission. 38 The reasons for this are not clear, but may relate to the complexity of immune responses in terms of genetic diversity of the human and parasite populations, and stochastic events associated with the induction of a specific antibody response.…”
Section: Discussionmentioning
confidence: 99%